Profile Secondary Metabolite Compounds and Antioxidant Activities of Stem Bark Jambu Mete (Anacardium occidantale L.) Extract - Tarso Rudiana; Dhyneu Dwi Jayanti; Siti Solehah (Jurnal Akademika Kimia, 2021)
Oxidative stress is a condition in which the amount of free radicals and antioxidants in the body is not balanced, causing various diseases. One of them is a degenerative disease. Oxidative stress can be reduced by antioxidant compounds. Anacardium occidentale L. is a type of plant from the Anacardiaceae family. This plant is found in many trophic countries included Indonesia, and is believed to ward off degenerative diseases caused by oxidative stress. The purpose of this study was to analyze the activity of A. occidentale stem bark extract against DPPH radical inhibition (1,1-Diphenyl-2-Picrilhidrazil) and the profiling of secondary metabolites in their active fraction. The bark of A. occidentale was extracted by a gradient maceration method. The solvents used were n-hexane (nonpolar), ethyl acetate (semi-polar), and methanol (polar). The macerate was concentrated using a rotary vacuum evaporator, followed by DPPH radical inhibition analysis using a spectrophotometer. The most active extract was analyzed for chemical content by LC-MS/MS. The results showed that the extract of A. occidentale stem bark had antioxidant activity. Methanol extract obtained very strong and best antioxidant activity with an IC50 value of 47.13 ppm compared to ethyl acetate extract and n-hexane extract, which had IC50 values of 163.92 ppm and 501.72 ppm, respectively. Secondary metabolites that are thought to have antioxidant activity in the methanol extract of A. occidentale stem bark were epigallocatechin (EC) and epigallocatechin gallate (EGCG) compounds.